2020
DOI: 10.1111/hir.12322
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and COVID‐19

Abstract: In early 2020, the world experienced an unprecedented health crisis. When the pandemic of coronavirus was declared by the World Health Organization, it brought with it sudden and dramatic changes to everyday life. In the UK, the key message from the Government was to ‘Stay at home, protect the NHS, save lives’, sending out a clear warning that failing to stay at home would put other lives and the ability of the NHS to cope at risk. This editorial discusses COVID‐19, how society responded and the vital role tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 0 publications
1
90
0
10
Order By: Relevance
“…Previous research also reported that HL in general helps identification of fake news 26 : this is especially true in crisis contexts like that generated by Covid-19. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research also reported that HL in general helps identification of fake news 26 : this is especially true in crisis contexts like that generated by Covid-19. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 15 Therefore, HL appears to be in close correlation with detection of fake news. Recent studies have explored separately the spread of fake news, 16 , 17 health literacy 18 , 19 and vaccine hesitancy 20 , 21 in the Covid-19 era, without the exploration of the interrelation of these three factors.…”
Section: Introductionmentioning
confidence: 99%
“…From the beginning of this pandemic, free and up-to-date learning materials have been available to almost anyone interested in learning more about COVID-19 ( World Health Organization, 2020c ). However, although social media and the Internet have been flooded with information about COVID-19, a significant proportion of it is inaccurate and sometimes misleading, indicating a deficiency in health literacy among the general population ( Spring, 2020 ). Hence, increasing the health literacy level of the general population will help to decrease the transmission of the virus ( Paakkari & Okan, 2020 ).…”
mentioning
confidence: 99%
“…Due to the exponential increase of its transmission and its devastating effects, many government heads advocated physical distancing and banned all social gatherings. The stay-at-home policy of virtually all the nations has helped in no small measure in combating the spread of the disease (Spring 2020). This is believed to break the chain and flatten the spread curve in no distant time until a certified vaccine is ready for use.…”
Section: The Surge Of Covid-19 Pandemic Humanmentioning
confidence: 99%
“…It is a truism that the surge of the Covid-19 pandemic and the associated crisis pose great challenges globally, whose impacts are intensely local; these indeed require global solidarity and coordination to curb the situation, according to economic experts (Spring 2020). This posits that human suffering is inevitable due to the pandemic, and many jobs and businesses will undoubtedly close.…”
Section: The Condition Posed By Covid-19 Pandemicmentioning
confidence: 99%